The Role of Community Participation in Mangrove Forest Conservation on Coastal Kaimana Regency West Papua - Kamakaula, Yohanes; Sagrim, Meky; Fenetiruma, Obadja Andris (West Science Nature and Technology, 2025)
This study examines the role of community participation in mangrove forest conservation in Kaimana Regency, West Papua, using a qualitative approach with five key informants, including local residents, community leaders, and environmental activists. Data were collected through in-depth interviews and field observations, then analyzed thematically. The findings reveal that community participation is central to mangrove conservation, manifested in activities such as planting, monitoring, and protecting mangroves from exploitation. Local wisdom and traditional norms, rooted in indigenous culture, serve as guiding principles that reinforce compliance and foster a collective sense of ownership. Nevertheless, challenges such as limited financial resources, lack of technical expertise, and external pressures from aquaculture and coastal development threaten the sustainability of these initiatives. Collaboration with NGOs, universities, and government agencies has strengthened local capacity, yet policy support remains inconsistent. This study concludes that integrating local wisdom, empowering communities, and fostering multi-stakeholder collaboration are essential strategies for effective and sustainable mangrove management in West Papua.